Are non-competitors greener? The effect of consumer awareness differences on green food consumption - Zheng, Manhua; Zheng, Qiujin; Chen, Jianhong; Tang, Decong (Frontiers in Psychology, 2023)
Introduction Green consumption plays a crucial role in mitigating environmental degradation. Governments and corporations are actively fostering the growth of green consumption. The escalating environmental issues have awakened consumers' environmental and competitive awareness, which significantly aids in increasing the probability of green food consumption. Methods This study, based on the Self-Consistency Theory and the Theory of Planned Behavior, constructs a model to analyze the effects of consumer competitive and environmental awareness on green food purchase intentions. Data from 700 consumer surveys were examined through structural equation modeling. Results Findings indicate that while consumer competitive awareness negatively impacts green self-efficacy and perceived control, environmental awareness has a positive effect. Green self-efficacy and perceived control both positively influence green food purchase intentions. Notably, competitive awareness has a more substantial negative impact on perceived control compared to green self-efficacy. In contrast, the positive influence of environmental awareness on green self-efficacy is stronger than on perceived control. Moreover, the effect of green self-efficacy on green food purchase intention is more pronounced than that of perceived control. Discussion Strategies like enhancing media publicity, educational initiatives, and improving purchase convenience can increase consumer purchase intentions. This study offers valuable insights for governments and businesses in understanding consumer psychology in green food consumption, aiding in marketing strategies for green food products.